5G – The Expectations and Enablers: 5G Expectations & Enablers - Naeem, Bushra; Ali, Raza; Shabbir, Bilal; Ali, Kamran (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
5G the fifth generation of mobile communication technology relies on a new network architecture that will be used to overcome the challenges faced in 4G technology. The current 4G Network architecture is unable to cater the increasing data traffic demand with very low latency rate. It is also not able to provide 100% network coverage. 5G technology will enable mobile users to experience the network with almost 100X better network capacity and coverage, very low latency and increased data traffic rates with new multiple radio access technology, improved radio network optimization and resource sharing. This paper provides an overview of key technology enablers that are imperative to ensure the promises of 5G.